Effects of incubation temperature and relative humidity on embryonic development in eggs of red-winged tinamou (Rhynchotus rufescens) - Boleli, Isabel Cristina [UNESP] (2012)
This study was conducted to assess the effects of incubation temperature (34°C, 36°C and 38°C) and relative humidity (RH, 50% and 60%) on egg weight loss, embryo mortality, hatchability, incubation time and chick weight in eggs from red-winged tinamou. The eggs were placed in incubators that were operated at 34°C, 36°C, or 38°C and 50% or 60% RH (mean wet bulb temperatures of 28°C and 30°C, respectively) from day 1 to hatching. Each treatment had two replicate groups of 30 eggs each. Hatchability varied with incubation temperature and RH and was highest for eggs incubated at 36°C and 60% RH and lowest for eggs incubated at 38°C. Early, intermediate and late embryo mortality were highest at 38°C, 38°C/50% RH, and 50% RH, respectively. Incubation period was longest at 34°C and shortest at 38°C/50% RH. Present results show the highest hatchability of red-winged tinamou eggs after incubation at 36°C and 60% RH; highest embryo sensitivity to high temperature in the early period of incubation (1 to 7 days), to high temperature and low RH in the second period of incubation (8-14 days) and to low RH in the late period of incubation (after 15 days) and shortest incubation period with increasing temperature and RH. © Asian Network for Scientific Information, 2012.